A tryparedoxin-dependent peroxidase protects African trypanosomes from membrane damage - Diechtierow, Michael; Krauth-Siegel, Renate (Free radical biology and medicine, 2011)
Hydroperoxide detoxification in African trypanosomes is achieved by 2-Cys-peroxiredoxin (TXNPx)- and non-selenium glutathione peroxidase (Px)-type enzymes which both obtain their reducing equivalents from the unique trypanothione/tryparedoxin system. Previous RNA interference approaches revealed that the cytosolic TXNPx and the Px-type enzymes are essential for Trypanosoma brucei. Because of partially overlapping in vitro substrate specificities and subcellular localisation the physiological function of the individual enzymes was not yet clear. As shown here, TXNPx and Px are expressed at comparable levels and in their active reduced state. Px-overexpressing parasites were less sensitive toward linoleic acid hydroperoxide but not hydrogen peroxide. Kinetic studies confirmed that Px—but not TXNPx—reduces lipophilic hydroperoxides including phospholipids with high efficiency. Most interestingly, the severe proliferation defect of Px-depleted bloodstream cells could be rescued by Trolox, but not by hydrophilic antioxidants, in the medium. This allowed us to knock-out the three Px genes individually and thus to distinguish their in vivo role. Deletion of the cytosolic Px I and II resulted in extremely fast membrane peroxidation followed by cell lysis. Cells lacking specifically the mitochondrial Px III showed a transient growth retardation and cardiolipin peroxidation but adapted within 24h to normal proliferation.
Gesehen am 10.05.2022